Anti‐p53 autoantibody in blood as a diagnostic biomarker for colorectal cancer: A meta‐analysis. (10th November 2019) - Liu, Shuxia; Tan, Qiaoyun; Song, Yuanyuan; Shi, Yuankai; Han, Xiaohong
Abstract: Serum autoantibodies against tumour‐associated antigens are promising biomarkers for diagnosis of cancer. This review summarizes the available evidence pertaining to the diagnostic potential of autoantibodies studied in the context of colorectal cancer (CRC). A systematic literature search was conducted in three databases (PubMed, Cochrane Library and Embase). Data pertaining to a total of 145 autoantibodies published in 80 articles were reviewed. Of these, anti‐p53 antibody was the most commonly studied autoantibody; thus, we performed a meta‐analysis on anti‐p53 antibody in 24 articles. According to the cut‐off values used to determine positivity for anti‐p53 antibody, we divided the included studies into five groups. Owing to the presence of threshold effect in groups 4 and 5 and non‐threshold effect in groups 1 and 2, pooled analysis focused on group 3 using a fixed‐effects model (Mantel‐Haenszel). Group 3, determining the cut‐off value based on the value of p53 antibody titre index, was comprised of five articles including 733 patients with CRC and 172 controls (126 healthy individuals and 46 benign diseases). The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio and summary area under the receiver operating characteristic curves were 0.21, 0.99, 12.26, 0.80, 15.46 and 0.87, respectively. Serum anti‐p53 autoantibody may potentially help distinguish CRC from healthy controls or benign diseases; however, it should be used in combination with other indicators due to the low sensitivity. Our study provides insights for further exploration of the optimal combination of different tumour‐associated antigens or autoantibodies for diagnosis of CRC.